Endometrial stromal sarcoma occurring 20 years after total hysterectomy for myomas - Yen-Feng Lu; Ben-Shian Huang; Chiung-Ru Lai; Kuan-Chin Wang; Ming-Shyen Yen; Peng-Hui Wang (Wolters Kluwer Medknow Publications, 2014)
Extrauterine and extraovarian endometrial stromal sarcomas (ESSs) without endometriosis are extremely rare. A 57-year-old woman had a pelvic mass. Twenty years previously, she had undergone total hysterectomy and left salpingo-oophorectomy for uterine myomas. A series of examinations, including upper and lower gastrointestinal evaluations, and tumor markers such as cancer antigen (CA)-125, CA 19-9, and carcinoembryonic antigen were all unremarkable; however, an 18-cm heterogeneous mass with strong enhancement and many surrounding engorged vessels was present in the pelvic computed tomography image. Exploratory laparotomy showed a 20-cm gray firm mass. A complete tumor excision was performed. Microscopic features showed abundant spindle cells and epithelioid-like cells with increased cellularity. Immunohistochemistry was strongly positive for CD10, FLI-1, and vimentin; weakly positive for estrogen and progesterone receptors; and negative for CD117, CD34, HMB45, alpha-inhibin, SMA, and S-100. This favored the diagnosis of ESS. The right ovary and fallopian tube, omentum, and pelvic lymph nodes were unremarkable. The patient was treated with 2-year hormone therapy (oral megestrol, 160 mg, taken daily) and radiation therapy (50.4 Gy, separated by 28 fractions). She has been disease-free for 3 years. Active management, including complete resection and hormone therapy with/without radiation is beneficial for women with extrauterine and extraovarian ESS.